A Broad-Spectrum Chemokine Inhibitor Drives M2 Macrophage Polarization Through Modulation of the Myometrial Secretome - Adam Boros-Rausch; Anna Dorogin; Lubna Nadeem; Oksana Shynlova; Stephen James Lye (Cells)
The uterine smooth muscle (myometrium) is an immunomodulatory tissue capable of secreting multiple chemokines during pregnancy. We propose that before term labor, chemokines secreted as a result of mechanical stretch of the uterine walls by the growing fetus(es) induce infiltration of maternal monocytes into myometrium, drive their differentiation into macrophages, and induce pro-inflammatory (M1) polarization, leading to labor contractions. This study used high-throughput proteomic mass-spectrometry to investigate the underlying mechanisms and explored the therapeutic potential of a broad-spectrum chemokine inhibitor (BSCI, FX125L) in modulating these effects. Primary myocytes isolated from the myometrium of term pregnant women were subjected in vitro to static mechanical stretch. Proteomic analysis of stretched myocyte-conditioned media (CM) identified significant upregulation of chemokine-related pathways and ECM degradation proteins. CM induced in vitro differentiation of human monocytes to macrophages and polarization into an M1-like phenotype characterized by elevated ROS production. BSCI treatment altered the myocyte secretome, increasing tissue-remodeling and anti-inflammatory proteins, Annexin A1 and TGF-β. BSCI-treated myocyte secretions induced Annexin A1 expression in macrophages and enhanced their phagocytic activity. We conclude that factors secreted by mechanically stretched myocytes induce pro-inflammatory M1 macrophage polarization, while BSCI modulates myocyte secretome, which reprograms macrophages to a homeostatic M2-like phenotype, thus reducing inflammation. When treated with BSCI, M2-polarized macrophages reduced myocyte-driven collagen gel contraction, whereas M1 macrophages enhanced it. This study reveals novel insights into the myocyte–macrophage interaction and identifies BSCI as a promising drug to modulate myometrial activity. We suggest that uterine macrophages may represent a therapeutic target for preventing preterm labor in women.